COMPARISON OF CLINICAL, METABOLIC AND ENDOCRINAL PARAMETERS OF OBESE AND LEAN POLYCYSTIC OVARY SYNDROME PATIENTS – CROSS-SECTIONAL ANALYTICAL STUDY (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Polycystic Ovary Syndrome (PCOS)-recently recognized by medical organizations as Polyendocrine Metabolic Ovarian Syndrome (PMOS)-is a common endocrine disorder affecting women of reproductive age and is frequently associated with obesity, which may aggravate its clinical, metabolic, and hormonal manifestations. This study aimed to compare the clinical, metabolic, and endocrinal parameters between obese and lean women with PMOS. Aim: To find out the differences in the clinical, metabolic, and endocrinal parameters among obese and lean PMOS. Methods: A hospital-based cross-sectional analytical study was conducted in the Department of Obstetrics and Gynaecology, College of Medicine and Sagore Dutta Hospital, Kolkata, among 120 women diagnosed with PMOS according to the Rotterdam criteria. Results: Obese PMOS women had significantly higher BMI and waist-to-height ratio than lean PMOS women (p